General characteristics of the mandatory social insurance (Journal of actual problems of jurisprudence, 2018)
In the state the general characteristic of compulsory social insurance. And also consider recent developmentsand shortcomings of social insurance. Social insurance – a system of social security, whose mission – toensure the constitutional rights of economically active citizens to maintenance in old age, in case of illness.Compulsory social security – part of the state system of social protection. The task today is to build a socialsecurity system that could quickly and raise living standards.Keywords: insurance, compulsory insurance, insurance relations, insurance companies.